Force of Infection Model for Estimating Time to Dengue Virus Seropositivity among Expatriate Populations, Thailand - Erica Rapheal; Amornphat Kitro; Hisham Imad; Marco Hamins-Peurtolas; Jutarmas Olanwijitwong; Lapakorn Chatapat; Taweewun Hunsawong; Kathryn Anderson; Watcharapong Piyaphanee (Emerging Infectious Diseases)
Dengue is a major cause of illness among local populations and travelers in dengue-endemic areas, particularly those who stay for an extended period. However, little is known about dengue risk among expatriates and other long-term travelers. We used catalytic models of force of infection to estimate time to 60% dengue virus (DENV) seropositivity for a cross-section of expatriates living in Bangkok and Pattaya, Thailand. Our model adjusted for daily time spent outside, years not exposed to DENV, sex, living environment, and use of mosquito repellent, nets, long sleeves, and air conditioning. We estimated an adjusted annual force of infection of 0.014 (95% CI 0.003–0.054) per year spent in dengue-endemic areas (67.3 years to 60% seropositivity), below that of local populations. Our findings suggest that expatriates have a DENV exposure profile distinct from locals and short-term travelers and should likely be considered independently when developing vaccine and prevention recommendations.